T Cell Activation Depends on Extracellular Alanine - Ron-Harel, Noga; Ghergurovich, Jonathan M.; Notarangelo, Giulia; LaFleur, Martin W.; Tsubosaka, Yoshiki; Sharpe, Arlene H.; Rabinowitz, Joshua D.; Haigis, Marcia C. (Cell reports (Cambridge), 2019)
T cell stimulation is metabolically demanding. To exit quiescence, T cells rely on environmental nutrients, including glucose and the amino acids glutamine, leucine, serine, and arginine. The expression of transporters for these nutrients is tightly regulated and required for T cell activation. In contrast to these amino acids, which are essential or require multi-step biosynthesis, alanine can be made from pyruvate by a single transamination. Here, we show that extracellular alanine is nevertheless required for efficient exit from quiescence during naive T cell activation and memory T cell restimulation. Alanine deprivation leads to metabolic and functional impairments. Mechanistically, this vulnerability reflects the low expression of alanine aminotransferase, the enzyme required for interconverting pyruvate and alanine, whereas activated T cells instead induce alanine transporters. Stable isotope tracing reveals that alanine is not catabolized but instead supports protein synthesis. Thus, T cells depend on exogenous alanine for protein synthesis and normal activation. [Display omitted] •Alanine is an essential amino acid for T cells to exit quiescence•Alanine deprivation during early activation leads to functional impairment•T cells do not catabolize alanine during early activation•Extracellular alanine supports protein synthesis In health, T lymphocytes are in a resting state. However, stimulation with their cognate antigen induces massive growth and proliferation. Ron-Harel et al. demonstrate that T cells rely on extracellular alanine for activation. Consumed alanine is used primarily for protein synthesis, and alanine deprivation inhibits T cell metabolism and effector functions.